Grammatical rule acquired versus learned in czech language acquisition by non-native speakers - Hrdlicka, Milan (Bohemica Olomucensia, 2019)
When acquiring knowledge of a language code (its grammatical system), either the mother tongue or foreign (or second), a major role is played by an intuitive, non-materialized, subjective grammatical rule acquired, as well as a cognitive, technical, explicitly formulated rule learned. A non-native speaker needs complex instructions about the target language, both about the formal aspect and the speech, functional and semantic dimension. Unfortunately, the latter is, more often than not, underestimated in textbooks of Czech for foreigners, there is significant room for improvement. A native speaker needs especially an instruction concerning the form of grammatical categories and phenomena (I am referring to the difference between the formal and the colloquial forms), but, in some cases, they also need an instruction about nuances in meaning (ctyri rocni obdobi - ctvero rocnich obdobi, etc.), which a native speaker often fails to differentiate. If a native speaker relies merely on their sensibility for language, they may find it difficult to describe in detail and explain on a satisfactory level the more advanced chapters of Czech grammar (the verb aspect, etc.).
Keywords: grammar; Czech for foreigners; grammatical rule; learning; acquisition; communicative method